Utilization of Predictive Models for Diagnosis of Occupational Diseases - Eva Suarthana; Mikhael Yosia (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Predictive models have long been used to assist clinical decision-making in medicine. Predictive models are made to estimate how likely a person is to have a disease (diagnostic model) or will experience a disease (prognostic model). In the field of occupational health, for example, diagnostic models can be used to increase the efficiency of surveillance programs by identifying groups of workers with occupational diseases without using complex and expensive diagnostic tests.Work-related asthma (WRA) is the most common occupational lung disease in industrialized countries and the second most common in developing countries. Around the world, especially in developing countries, diagnosing WRA is still difficult due to the limitations of available diagnostic tests. Specific inhalation challenge (SIC), the best test for diagnosing occupational asthma, is only available in several research centres worldwide.Several questionnaire-based models have been developed to diagnose work-related asthma at both the primary (general practitioner) and secondary (specialist) levels of care. A recent model for diagnosing occupational asthma was developed using data from Canada and has been validated using data from several European countries. A collaboration has been initiated to assess the application of this model among Indonesian workers.